Analysis of Project Owner Satisfaction on the Performance of Supervisory Consultants on Road Construction Projects at Road and Bridge Maintenance Section of the Banjarbaru City Public Works Service, South Kalimantan - Apriani, Rusna; Prasetia, Irfan (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
During the outbreak of Covid-19 disease, the Banjarbaru City Government allocates most of the APBD funds for handling Covid-19 (Refocusing) including funds for the implementation of road infrastructure from 2020 until 2021. For efficiency, the step taken is to combine several streets on different packages to become one with the same supervisory consultant package. Based on data, supervisory consultants are mostly domiciled outside Banjarbaru City. In addition viewed of the project location which supervised, location packages of construction work are quite far away from each other. In this Covid-19 pandemic condition, Banjarbaru city participated in implementing restrictions on community activities (PPKM) by blocking several city entry points. With these restrictions, communication between supervisory consultants and project owners during the implementation of work is less effective because mostly implemented online so that it can affect the performance of most supervisory consultants. Therefore, an analysis of job owner satisfaction with the performance of supervisory consultants on road construction in Banjarbaru City needs to be done, especially in this Covid-19 era. The study was conducted by collecting primary data obtained through questionnaires on a sample of sources at Dinas Pekerjaan Umum Kota Banjarbaru (Cipta Karya & Bina Marga). Data were analyzed using the computer program SPSS version 26.00 (Statistical Product and Service Solution). To determine the level of participant satisfaction, the Customer Satisfaction Index (CSI) method is used. Meanwhile, to determine the service factors that need to be improved, the Importance Performance Analysis (IPA) method is used. The results of the respondents' answers in the questionnaire will be analyzed by using Importance Performance Analysis (IPA). Variables that located in zone A or the main priority will be the focus of determining the performance improvement strategy of supervisory consultants. Based on an analysis of 3(three) indicators with the following levels of satisfaction: Administrative Indicators of 68.84% (Satisfied), Monitoring Indicators of 74.81% (Satisfied), and Ability Indicators of 73.78% (Satisfied). Based on the analysis results, the dominant factors in improving performance, including in quadrant A, are the reporting of work progress activities and reporting of the results of the supervisory consultant activities, the supervision factor for the work method of construction during Covid-19, the ability factor to be present in the midst of the government's policy of enforcing the Enforcement of Restrictions on Community Activities (PPKM) and the factor of communication and coordination ability with the project owner by minimizing direct contact (Virtual).